Rheumatic fever–exacerbation or decline? Analysis of patients admitted to a medical service within a period of 20 years. - Morais, F; Silva, G N; Santos, R M; Sousa, J T; Saavedra, J A; Da Costa, J N (Acta Médica Portuguesa, 1989)
The authors revised 116 clinical files of patients admitted to a Medicine ward with Rheumatic Fever in the years 1959-63 and 1979-83, in order to detect a possible recrudescence of the disease. The following parameters were analysed: age, sex, length of hospital stay, clinical manifestations, ancillary exams, therapeutics and evolution. It was found an impressive decline in the incidence of the disease (90 cases vs 26) and also a very significant decrease of the period of hospitalization in the recent group of patients (p less than 0.0005); Carditis and relapses of Rheumatic Fever were more frequent in the old group of patients.